2016
DOI: 10.1556/2006.5.2016.025
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Pathways to Compulsive Buying in Chinese College Students in Hong Kong and Macau

Abstract: Background and aimsThe addictive nature of compulsive buying implies that mood disturbances, stress, and cognitive biases that underlie compulsive buying might operate in ways similar in both genders. In the current study, we aimed to test hypothetical pathways of mood compensation and irrational cognitions, which may explain compulsive buying tendencies. We also examined potential gender differences in these pathways.MethodsTwo-hundred and thirty-two male (age: M = 20.30, SD = 1.74) and 373 female Chinese col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 77 publications
3
15
0
3
Order By: Relevance
“…Different characteristics of the subjects may be the cause of these differences. In addition, in comparison to some of the unselected/control populations in previous studies using the same scale-DASS21, we found that the total DASS score in our study do appear to be elevated which can partly proved that IUA patients had a relatively high level of psychological distress [20][21][22][23]. Furthermore, patients who had a history of chronic anxiety or depression (or prior medication for either) had been excluded, which means that levels of anxiety and depression PLOS ONE Table 1.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Different characteristics of the subjects may be the cause of these differences. In addition, in comparison to some of the unselected/control populations in previous studies using the same scale-DASS21, we found that the total DASS score in our study do appear to be elevated which can partly proved that IUA patients had a relatively high level of psychological distress [20][21][22][23]. Furthermore, patients who had a history of chronic anxiety or depression (or prior medication for either) had been excluded, which means that levels of anxiety and depression PLOS ONE Table 1.…”
Section: Discussionsupporting
confidence: 62%
“…High scores suggest that the symptomatology is severe. The recommended cut-offs points for each subscale are as follows: depression [normal (0-9), mild (10)(11)(12)(13), moderate (14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27), and extremely severe (28+)], anxiety [normal (0-7), mild (8-9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), and extremely severe (20+)], and stress [normal (0-14), mild (15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25), severe (26)(27)(28)(29)(30)(31)(32)(33), and extremely severe (34+)] [14,…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have indicated that the socio-cultural context and economic development might be critical factors influencing CB [4, 5]. Although several recent studies have investigated CB behavior with Chinese samples in Hong Kong and Macau [6], Taiwan [7] as well as China mainland [8], almost the entirety of knowledge in this area has been developed from samples in western developed countries, for example the United States, Germany, etc. [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…They expressed more desire for luxurious goods, and believed more strongly that money will bring them happiness. Furthermore, they also reported significantly more liking of shopping in general and peer-status related consumption in particular (Chan, 2010).…”
Section: Materialismmentioning
confidence: 94%
“…The MVS is one of the most widely used measure of materialism, and its validity has been tested in many cross‐cultural studies, including those with Chinese individuals (e.g. Ching, Tang, Wu, & Yan, ). Participants responded to statements such as I'd be happier if I could afford to buy more things , and indicated their agreement on a 5‐point Likert style scale from strongly disagree (1) to strongly agree (5).…”
Section: Studymentioning
confidence: 99%